Development of X-SIAGA: A disease X and outbreak preparedness intervention for indigenous households in Selangor, Malaysia - Ameerah Su’ad Abdul Shakor; Mariam Mohamad; Khalid Ibrahim; Izandis Mohamad Sayed (PLoS ONE, 2026)
Background The indigenous people of Peninsular Malaysia, locally known as the Orang Asli, are vulnerable to outbreaks and novel threats such as Disease X. This is due to socioeconomic challenges, limited healthcare access, and exposure to zoonotic spillover. Outbreaks in this community often result in fatalities, yet their interest in preparedness is low and no tailored intervention exists. This study describes the development of X-SIAGA, an intervention to improve household-level preparedness for Disease X and outbreaks among the Orang Asli in Selangor using the Intervention Mapping (IM) approach, a systematic framework for developing theory‑ and evidence‑based health interventions. Methods The six-step IM framework was applied: needs assessment, setting program goals, selecting intervention methods, developing components, implementation planning, and program evaluation. Evaluation involved validation of X-SIAGA and its measurement tool, Household Outbreak Preparedness Evaluation (HOPE) questionnaire, with experts (n = 5) and community members (n = 14), and a pilot test (n = 18) to assess its acceptability and preliminary effectiveness. Results Needs assessment confirmed the necessity of a tailored intervention for outbreak and Disease X household preparedness. Findings guided the development of logic models, outcomes, and objectives. Both X-SIAGA and HOPE showed high content and face validity (validity indexes 0.97 to 1.0). The pilot test showed high acceptability (83.3%), and HOPE measured a significant improvement in household preparedness following X-SIAGA (mean difference = 0.22, 95% CI = 0.17–0.27, p < 0.001, Cohen’s d = 1.99). Conclusion X-SIAGA is a comprehensive, evidence- and theory-based intervention designed to improve household preparedness for Disease X and outbreaks among the Orang Asli in Selangor. It is valid, feasible, and acceptable in the community. X-SIAGA shows promise and is ready for full-scale trial evaluation and long-term assessment, with potential for adaptation in other communities.